The impacts of tourism on cultural identity on Lisbon Historic Neighbourhoods - Daly, P. (2020)
In the past last decades tourism was long perceived as a solution to remediate to economic crisis and recessions, while the impacts were secondary and weren’t qualified. Focusing of the consequences of tourism development, the identities of historic urban areas were constantly been neglected as essential features and symbols of their attractiveness. However, long before tourism, modifications of cities spatial structures and social geography were conducted by governments as strategies to repopulate certain urban areas abandoned for historical or economic reasons. For instance, through gentrification, urban rehabilitation or revitalisation, the urban structures became more appealing and attracted investments that strengthen local economies. Nevertheless, these transformations have dismantled cultural patterns and were amplified by touristification. This investigation deals with gentrification and urban rehabilitation as precursors of tourism growth and how it influences a neighbourhood’s cultural identity. Using a historic touristic destination as an example gave leverage to the understanding of the repercussions. Lisbon historic neighbourhoods; Alfama, Mouraria and Bairro Alto, influenced our understanding with the active participation of the residents as co-contributors of this research. Findings confronted our pre-existing understandings on tourism growth to the impacts generated on cultural identity.